A key to American genus Merobruchus Bridwell (Coleoptera: Chrysomelidae: Bruchinae) with descriptions of species and two new host plant records for the subfamily - Manfio, Daiara; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2016)
Merobruchus Bridwell is placed in the group Merobruchus of Acanthoscelidina (Bruchini) being distinguished from all bruchines mainly by the apical projections in the last abdominal ventrite of females and some males. All 25 species of Merobruchus are distributed in the New World, mainly in the Neotropical Region, feeding on seeds of Mimosoideae (Acacieae, Ingeae and Mimoseae). As well as some other bruchine genera, Merobruchus shows considerable morphological variation both in external and in internal (male genitalia) characters. Moreover, some species are very similar to each other in their colour and distribution pattern of pubescence on the dorsal surface, sometimes making species recognition difficult. Thus, the main objective of this paper is to provide a key including coloured illustrations for Merobruchus species to facilitate the process of identification and to avoid misunderstandings. Images of dorsal habitus, male and female pygidium and male genitalia are provided for all species. In addition, M. machadoi sp. nov. (Holotype male deposited in DZUP: Brazil, Rio Grande do Sul State) is described; M. bicoloripes (Pic) and M. pickeli (Pic) are redescribed; and a new synonymy is proposed: Pseudopachymerus pickeli Pic, 1927 = Pseudopachymerus pickeli var. subnotatus Pic, 1927 syn. nov. Two new host plants are recorded for Bruchinae: Parapiptadenia rigida (Benth.) Brenan (Mimosoideae) and Pterogyne nitens Tul. (Caesalpinioideae).